The Dynamic Change of Pore Structure for the Low-Rank Coal with Various Pretreatment Temperatures: A Case Study from Southwestern Ordos Basin. (1st July 2020) - Li, Teng
Abstract : The pore characteristics of the low-rank coal are different from medium- and high-rank coals. The low-temperature N2 adsorption (LP-N2 A) measurements with a single low-rank coal were launched, and the dynamic change of pore structures under various pretreatment temperatures from 120°C to 300°C was studied. The isothermal curves of the DFS coal sample feature IV type, the hysteresis loops convert from H4 type to H2 type, and the hysteresis loops tend to be closed with the increased pretreatment temperatures. The mesopores are dominant in the DFS coal. The dynamic of pore volume (PV) and pore specific surface area (SSA) features the three-step-style change with the cut-off temperature points at 150°C and 240°C, and this has a relationship with the loss of the moisture and volatiles in the DFS coal sample. The pores with an aperture below 10 nm are the dominant mesopores in the DFS coal, and the mesopore volume features bimodal pattern distribution with a higher left peak of approximately 1.7 nm and a lower right peak of approximately 3-5 nm, and the right peak continuously right shift with the increase pretreatment temperatures. The total mesopore volume decreases with the upgrading temperatures, while the ratio of pores greater than 5 nm increases. Finally, the mesopore evolution model with the increased pretreatment temperatures was summarized.